2015
DOI: 10.1021/acs.jmedchem.5b00516
|View full text |Cite
|
Sign up to set email alerts
|

Functional Profiling of 2-Aminopyrimidine Histamine H4 Receptor Modulators

Abstract: Histamine is an important endogenous signaling molecule that is involved in a number of physiological processes including allergic reactions, gastric acid secretion, neurotransmitter release, and inflammation. The biological effects of histamine are mediated by four histamine receptors with distinct functions and distribution profiles (H1-H4). The most recently discovered histamine receptor (H4) has emerged as a promising drug target for treating inflammatory diseases. A detailed understanding of the role of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…[207][208][209][210]245 To improve the translational value of animal models, new molecular tools for the H 4 R are needed, comprising balanced functional profiles across the species with a special emphasis on the most important laboratory animals like mice and rats. With 2,4-diaminopyrimidine-type agonists [246][247][248] (example see Figure 1.5) and antagonists [e.g. JNJ-39758979, (Figure 1.…”
Section: The (Patho)physiological Role Of the H 4 R And Clinical Candidatesmentioning
confidence: 99%
“…[207][208][209][210]245 To improve the translational value of animal models, new molecular tools for the H 4 R are needed, comprising balanced functional profiles across the species with a special emphasis on the most important laboratory animals like mice and rats. With 2,4-diaminopyrimidine-type agonists [246][247][248] (example see Figure 1.5) and antagonists [e.g. JNJ-39758979, (Figure 1.…”
Section: The (Patho)physiological Role Of the H 4 R And Clinical Candidatesmentioning
confidence: 99%
“…The human histamine H 4 receptor (hH 4 R) was discovered at the turn of the millennium as the latest member of the histamine receptor family (H 1–4 Rs) and is expected to be a promising target for the treatment of disorders of the immune system (e.g., rheumatoid arthritis, bronchial asthma). , The expression and a potential physiological role of the H 4 R in the brain was controversially discussed in the literature . For investigations on the (patho)­physiology of the H 4 R, mouse and rat became the most important laboratory animals . However, the pharmacological evaluation of the rodent histamine H 4 receptors (mH 4 R, rH 4 R) is compromised by species-dependent discrepancies regarding the potencies (e.g., 1 , 2 , and 3 ) and/or the quality of action (e.g., 4 , 5, and 6 ) of standard ligands for the hH 4 R (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Many examples of speciation that have impacted drug discovery efforts exist in the literature and cover a broad range of protein families including G protein-coupled receptors (27), cytochrome P450 isoforms (28), and the MAPEG member microsomal prostaglandin E synthase-1 (29), for example. In the simplest of cases, research teams have identified an appropriate preclinical species, with homologous target protein sequence to human, to enable translational models.…”
Section: Discussionmentioning
confidence: 99%